Pilot Study of Two Nurse-Led Weaning Protocols in Patients with Tracheostomies. (January 2014) - Pattani, Hina; Ehlers, Mark; Girling, Keith; Hird, Caroline; Gardiner, Dale
This is a pilot study, comparing two commonly-used weaning techniques in patients with a tracheostomy to establish if one technique resulted in shorter time to successful weaning. In a prospective, single-centre randomised, controlled trial, conducted in a 15-bed multidisciplinary intensive care unit, fifty patients mechanically ventilated for at least 48 hours and who had a tracheostomy inserted primarily for weaning purposes, were randomised to one of two weaning techniques: increasing periods of spontaneous ventilation, or reducing pressure support ventilation. Each technique was protocolised for implementation by the nursing staff and consisted of two stages: a weaning and a verification stage. This pilot study did not find a statistically significant difference in the length of time spent weaning when two nurse-led protocolised weaning techniques of increasing periods of spontaneous ventilation or reducing pressure support ventilation were compared in patients with a tracheostomy inserted primarily for weaning purposes. No safety issues were identified in either protocol.